A Contrast of U.S. Metropolitan Demographic Poverty: Chicago, Los Angeles, and New York. (18th October 2011) - Mogull, Robert G.
Abstract : This paper examines and compares U.S. poverty rates on two levels, with data obtained from the decennial censuses of 1960 through 2000. First, rates of poverty for five demographic groups are contrasted within each of the three most populous metropolises of the nation—Chicago, Los Angeles/Long Beach, and New York. Second, rates for each demographic group are contrasted among the three metropolises. The statistical evidence reveals both large differences among the individual demographic groups and also in the trends among the three most populous American cities.